miR-7 and miR-218 epigenetically control tumor suppressor genes RASSF1A and Claudin-6 by targeting HoxB3 in breast cancer - Li, Qiaoyan; Zhu, Fufan; Chen, Puxiang (Biochemical and biophysical research communications, 2012)
► Both miR-7 and miR-218 down-regulates HoxB3 expression by targeting the 3′-UTR of HoxB3 mRNA. ► A reverse correlation between the levels of endogenous miR-7, miR218 and HoxB3 expression. ► Epigenetic changes involve in the reactivation of HoxB3. ► Both miRNAs inhibits the cell cycle and clone formation of breast cancer cells. Many microRNAs have been implicated as key regulators of cellular growth and differentiation and have been found to dysregulate proliferation in human tumors, including breast cancer. Cancer-linked microRNAs also alter the epigenetic landscape by way of DNA methylation and post-translational modifications of histones. Aberrations in Hox gene expression are important for oncogene or tumor suppressor during abnormal development and malignancy. Although recent studies suggest that HoxB3 is critical in breast cancer, the putative role(s) of microRNAs impinging on HoxB3 is not yet fully understood. In this study, we found that the expression levels of miR-7 and miR-218 were strongly and reversely associated with HoxB3 expression. Stable overexpression of miR-7 and miR-218 was accompanied by reactivation of tumor suppressor genes including RASSF1A and Claudin-6 by means of epigenetic switches in DNA methylation and histone modification, giving rise to inhibition of the cell cycle and clone formation of breast cancer cells. The current study provides a novel link between overexpression of collinear Hox genes and multiple microRNAs in human breast malignancy.